Anti-static coating and preparation method thereof
By using epoxy resin, perfluorosulfonic acid resin and polyaniline modified carbon nanotubes in anti-static coatings and combining the cross-linking network structure of hydroxypropyl methylcellulose, the problem of poor dispersion of carbon nanotubes is solved, and the anti-static and surface mechanical properties of the coating are significantly improved.
Patent Information
- Application Number
- CN202411694526.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When carbon nanotubes are used as conductive agents in existing anti-static coatings, they have poor dispersion and are prone to agglomeration, which affects the surface mechanical properties and anti-static properties of the coating.
Epoxy resin and perfluorosulfonic acid resin are used as resin matrix, and the carbon nanotubes are modified by polyaniline modification, combined with hydroxypropyl methylcellulose and the carbon nanotubes are cross-linked to form a stable network structure and improve the dispersion of the carbon nanotubes.
It effectively alleviates the agglomeration of carbon nanotubes, improves its dispersion in the resin matrix, and significantly improves the surface mechanical properties and anti-static properties of the coating.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to an antistatic coating and a preparation method thereof. Background Art
[0002] Antistatic coating refers to a type of functional coating that is applied to the substrate and has the ability to conduct current and eliminate accumulated static charges. With the rapid development of technology, antistatic coatings have been widely used in various military and civilian industrial fields such as electronics, aviation, chemicals, and printing.
[0003] At present, antistatic coatings usually need to add conductive agents to obtain good antistatic effects. Carbon nanotubes are commonly used conductive agents due to their good conductivity and structural characteristics. However, due to the large specific surface area of carbon nanotubes, as well as the structure, size, and interface interaction with the substrate resin, the dispersion of carbon nanotubes will be affected, causing them to easily agglomerate, making it difficult to disperse evenly in the substrate resin. Agglomerated carbon nanotubes will easily form small particles on the surface of antistatic coatings, affecting the surface mechanical properties and antistatic properties. Summary of the invention
[0004] In view of the problem that the antistatic coatings using carbon nanotubes as conductive agents in the prior art generally have poor dispersion of the carbon nanotubes and are easy to agglomerate, thereby affecting the surface mechanical properties and antistatic properties of the coatings, the present invention provides an antistatic coating, which uses epoxy resin and perfluorosulfonic acid resin as resin matrices, polyaniline-modified carbon nanotubes, and uses hydroxypropyl methylcellulose to cross-link with the carbon nanotubes to form a stable network structure, which can effectively alleviate the agglomeration of the carbon nanotubes and improve their dispersibility in the resin matrix. The coating finally obtained exhibits excellent surface mechanical properties and antistatic properties.
[0005] The first aspect of the present invention provides an antistatic coating, which comprises the following components by weight: 20 to 40 parts of epoxy resin, 10 to 15 parts of perfluorosulfonic acid resin, 1 to 3 parts of hydroxypropyl methylcellulose, 0.5 to 2 parts of polyaniline modified carbon nanotubes, 1 to 2 parts of curing agent, 0.5 to 5 parts of dispersant, 3 to 5 parts of leveling agent, and 55 to 70 parts of solvent.
[0006] Furthermore, the preparation method of polyaniline modified carbon nanotubes is: The carbon nanotubes are placed in a mixed solution of concentrated sulfuric acid and concentrated nitric acid, subjected to ultrasonic treatment, and then filtered and washed until the filtrate is neutral, dried, ground, and set aside to obtain pretreated carbon nanotubes; Add aniline to 0.5-2 wt% concentrated sulfuric acid and stir thoroughly for 1-2 hours to obtain an acidic solution of aniline; The pretreated carbon nanotubes were added into an acidic solution of aniline at 1-3 wt%, ultrasonically dispersed for 2-3 hours, and then ammonium persulfate was added and ultrasonicated for 1-2 hours to obtain polyaniline-modified carbon nanotubes.
[0007] Furthermore, the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1.
[0008] Furthermore, the mass ratio of carbon nanotubes to ammonium persulfate is 1:5-10.
[0009] Furthermore, the epoxy resin is at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, polyphenol glycidyl ether epoxy resin, aliphatic glycidyl ether epoxy resin, glycidyl ester epoxy resin, and heterocyclic epoxy resin.
[0010] Furthermore, the curing agent is an isocyanate curing agent.
[0011] Furthermore, the dispersant is at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and polyvinyl pyrrolidone.
[0012] Furthermore, the leveling agent is any one of leveling agent GLP388, leveling agent GLP588, and leveling agent GLP788.
[0013] Furthermore, the solvent is a mixture of polyvinyl alcohol, n-butanol and deionized water, and the volume ratio of polyvinyl alcohol, n-butanol and deionized water is 2:5:3.
[0014] The second aspect of the present invention provides a method for preparing the above-mentioned antistatic coating, comprising the following steps: S1: mixing hydroxypropyl methylcellulose and polyaniline-modified carbon nanotubes, grinding them, dissolving them in a dispersant, and stirring them for 0.5-1h to obtain a mixed solution A; S2: dissolving epoxy resin and perfluorosulfonic acid resin in a solvent and stirring for 0.5-1h to form a mixed solution B; S3: Mix the mixed liquid A and the mixed liquid B, continue stirring for 2-3 hours, add the curing agent and the leveling agent during the stirring process, and place at 40-45°C for 1-2 hours after the stirring to obtain the antistatic coating.
[0015] Furthermore, the stirring process is carried out in a mixer at a stirring speed of 400-550 r / min.
[0016] The beneficial effects achieved by one or more technical solutions of the present invention are as follows: 1. The present invention adopts epoxy resin and perfluorosulfonic acid resin as the resin matrix. The sulfonic acid group of the perfluorosulfonic acid resin is easy to undergo a grafting reaction with the amino group of polyaniline on the carbon nanotubes, so that the carbon nanotubes can obtain stronger adhesion between the interface of the resin matrix, promote the carbon nanotubes to be better dispersed between the base resins, inhibit the agglomeration effect of the carbon nanotubes, and thus effectively improve the antistatic performance of the coating.
[0017] 2. The present invention uses hydroxypropyl methylcellulose as the reinforcing phase in the system, which can cross-link with carbon nanotubes to form a stable network structure, further maintaining the dispersibility of the carbon nanotubes, making the structure of the entire system more stable, and significantly improving the surface mechanical properties of the coating. DETAILED DESCRIPTION
[0018] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.
[0019] Example 1 The present embodiment provides an antistatic coating, which includes the following components by weight: 20 parts of bisphenol A epoxy resin, 10 parts of perfluorosulfonic acid resin, 1 part of hydroxypropyl methylcellulose, 0.5 parts of polyaniline-modified carbon nanotubes, 1 part of isocyanate curing agent XP2655, 0.5 parts of sodium lauryl sulfate, 3 parts of leveling agent GLP388, and 55 parts of solvent; The solvent is a mixture of polyvinyl alcohol, n-butanol and deionized water in a volume ratio of 2:5:3.
[0020] The preparation method is as follows: S1: placing the carbon nanotubes in a mixture of concentrated sulfuric acid and concentrated nitric acid (the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1), ultrasonically treating, then filtering, washing until the filtrate is neutral, drying, grinding, and setting aside to obtain pretreated carbon nanotubes; S2: Add aniline to 1 wt% concentrated sulfuric acid and stir for 2 h to obtain an acidic solution of aniline; S3: adding the pretreated carbon nanotubes to an acidic solution of aniline at 2 wt%, ultrasonically dispersing for 3 h, then adding ammonium persulfate and continuing ultrasonication for 2 h (the mass ratio of carbon nanotubes to ammonium persulfate is 1:5), to obtain polyaniline-modified carbon nanotubes; S4: mixing hydroxypropyl methylcellulose and polyaniline-modified carbon nanotubes, grinding them, dissolving them in sodium dodecyl sulfate, and stirring them in a stirrer for 1 hour at a stirring speed of 550 r / min to obtain a mixed solution A; S5: dissolving epoxy resin and perfluorosulfonic acid resin in a solvent, stirring in a mixer for 0.5 to 1 h at a stirring speed of 550 r / min to form a mixed solution B; S6: Mix the mixed solution A and the mixed solution B, continue stirring for 3 hours, add a curing agent and a leveling agent during the stirring process, and place at 45° C. for 2 hours after the stirring to obtain an antistatic coating.
[0021] Example 2 The present embodiment provides an antistatic coating, which includes the following components by weight: 30 parts of bisphenol F epoxy resin, 10 parts of perfluorosulfonic acid resin, 1 part of hydroxypropyl methylcellulose, 1 part of polyaniline modified carbon nanotubes, 2 parts of isocyanate curing agent XP2655, 3 parts of sodium dodecyl sulfate, 4 parts of leveling agent GLP588, and 65 parts of solvent; The solvent is a mixture of polyvinyl alcohol, n-butanol and deionized water in a volume ratio of 2:5:3.
[0022] The preparation method is as follows: S1: placing the carbon nanotubes in a mixture of concentrated sulfuric acid and concentrated nitric acid (the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1), ultrasonically treating, then filtering, washing until the filtrate is neutral, drying, grinding, and setting aside to obtain pretreated carbon nanotubes; S2: Add aniline to 0.5 wt% concentrated sulfuric acid and stir thoroughly for 1 h to obtain an acidic solution of aniline; S3: adding the pretreated carbon nanotubes at 1 wt% into an acidic solution of aniline, ultrasonically dispersing for 3 h, then adding ammonium persulfate and continuing ultrasonication for 2 h (the mass ratio of carbon nanotubes to ammonium persulfate is 1:8), to obtain polyaniline-modified carbon nanotubes; S4: mixing hydroxypropyl methylcellulose and polyaniline-modified carbon nanotubes, grinding them, dissolving them in sodium dodecyl sulfate, and stirring them in a stirrer for 0.5 h at a stirring speed of 550 r / min to obtain a mixed solution A; S5: dissolving epoxy resin and perfluorosulfonic acid resin in a solvent, stirring in a mixer for 1 h at a stirring speed of 550 r / min to form a mixed solution B; S6: Mix the mixed solution A and the mixed solution B, continue stirring for 3 hours, add a curing agent and a leveling agent during the stirring process, and place at 45° C. for 2 hours after the stirring to obtain an antistatic coating.
[0023] Example 3 The present embodiment provides an antistatic coating, which includes the following components by weight: 30 parts of bisphenol A epoxy resin, 10 parts of perfluorosulfonic acid resin, 2 parts of hydroxypropyl methylcellulose, 1 part of polyaniline-modified carbon nanotubes, 1 part of isocyanate curing agent XP2655, 2 parts of sodium dodecylbenzene sulfonate, 3 parts of leveling agent GLP388, and 60 parts of solvent; The solvent is a mixture of polyvinyl alcohol, n-butanol and deionized water in a volume ratio of 2:5:3.
[0024] The preparation method is as follows: S1: placing the carbon nanotubes in a mixture of concentrated sulfuric acid and concentrated nitric acid (the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1), ultrasonically treating, then filtering, washing until the filtrate is neutral, drying, grinding, and setting aside to obtain pretreated carbon nanotubes; S2: Add aniline to 1wt% concentrated sulfuric acid and stir thoroughly for 1h to obtain an acidic solution of aniline; S3: adding the pretreated carbon nanotubes to an acidic solution of aniline at 1 wt%, ultrasonically dispersing for 2 h, then adding ammonium persulfate and continuing ultrasonication for 1 h (the mass ratio of carbon nanotubes to ammonium persulfate is 1:5), to obtain polyaniline-modified carbon nanotubes; S4: mixing hydroxypropyl methylcellulose and polyaniline-modified carbon nanotubes, grinding them, dissolving them in sodium dodecylbenzene sulfonate, and stirring them in a stirrer for 0.5 h at a stirring speed of 400 r / min to obtain a mixed solution A; S5: dissolving epoxy resin and perfluorosulfonic acid resin in a solvent, stirring in a stirrer for 0.5 h at a stirring speed of 400 r / min to form a mixed solution B; S6: Mix the mixed solution A and the mixed solution B, continue stirring for 2 hours, add a curing agent and a leveling agent during the stirring process, and place at 40° C. for 2 hours after the stirring to obtain an antistatic coating.
[0025] Example 4 The present embodiment provides an antistatic coating, which comprises the following components by weight: 40 parts of bisphenol F epoxy resin, 15 parts of perfluorosulfonic acid resin, 3 parts of hydroxypropyl methylcellulose, 2 parts of polyaniline-modified carbon nanotubes, 2 parts of isocyanate curing agent XP2655, 5 parts of polyvinyl pyrrolidone, 5 parts of leveling agent GLP788, and 70 parts of solvent; The solvent is a mixture of polyvinyl alcohol, n-butanol and deionized water in a volume ratio of 2:5:3.
[0026] The preparation method is as follows: S1: placing the carbon nanotubes in a mixture of concentrated sulfuric acid and concentrated nitric acid (the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1), ultrasonically treating, then filtering, washing until the filtrate is neutral, drying, grinding, and setting aside to obtain pretreated carbon nanotubes; S2: Add aniline to 2 wt% concentrated sulfuric acid and stir for 2 h to obtain an acidic solution of aniline; S3: adding the pretreated carbon nanotubes to an acidic solution of aniline at 3 wt%, ultrasonically dispersing for 3 h, then adding ammonium persulfate and continuing ultrasonication for 2 h (the mass ratio of carbon nanotubes to ammonium persulfate is 1:10), to obtain polyaniline-modified carbon nanotubes; S4: mixing hydroxypropyl methylcellulose and polyaniline-modified carbon nanotubes, grinding them, dissolving them in polyvinyl pyrrolidone, and stirring them in a stirrer for 1 hour at a stirring speed of 500 r / min to obtain a mixed solution A; S5: dissolving epoxy resin and perfluorosulfonic acid resin in a solvent, stirring in a mixer for 1 h at a stirring speed of 500 r / min to form a mixed solution B; S6: Mix the mixed solution A and the mixed solution B, continue stirring for 3 hours, add a curing agent and a leveling agent during the stirring process, and place at 45° C. for 2 hours after the stirring to obtain an antistatic coating.
[0027] Comparative Example 1 This comparative example provides an antistatic coating, which includes the following components by weight: 30 parts of bisphenol A epoxy resin, 2 parts of hydroxypropyl methylcellulose, 1 part of polyaniline modified carbon nanotubes, 1 part of isocyanate curing agent XP2655, 2 parts of sodium dodecylbenzene sulfonate, 3 parts of leveling agent GLP388, and 60 parts of solvent; The solvent is a mixture of polyvinyl alcohol, n-butanol and deionized water in a volume ratio of 2:5:3.
[0028] The preparation method is as follows: S1: placing the carbon nanotubes in a mixture of concentrated sulfuric acid and concentrated nitric acid (the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1), ultrasonically treating, then filtering, washing until the filtrate is neutral, drying, grinding, and setting aside to obtain pretreated carbon nanotubes; S2: Add aniline to 1wt% concentrated sulfuric acid and stir thoroughly for 1h to obtain an acidic solution of aniline; S3: adding the pretreated carbon nanotubes to an acidic solution of aniline at 1 wt%, ultrasonically dispersing for 2 h, then adding ammonium persulfate and continuing ultrasonication for 1 h (the mass ratio of carbon nanotubes to ammonium persulfate is 1:5), to obtain polyaniline-modified carbon nanotubes; S4: mixing hydroxypropyl methylcellulose and polyaniline-modified carbon nanotubes, grinding them, dissolving them in sodium dodecylbenzene sulfonate, and stirring them in a stirrer for 0.5 h at a stirring speed of 400 r / min to obtain a mixed solution A; S5: dissolving the epoxy resin in the solvent, stirring in a stirrer for 0.5 h at a stirring speed of 400 r / min to form a mixed solution B; S6: Mix the mixed solution A and the mixed solution B, continue stirring for 2 hours, add a curing agent and a leveling agent during the stirring process, and place at 40° C. for 2 hours after the stirring to obtain an antistatic coating.
[0029] Comparative Example 2 This embodiment provides an antistatic coating, which includes the following components by weight: 30 parts of bisphenol A epoxy resin, 10 parts of perfluorosulfonic acid resin, 2 parts of hydroxypropyl methylcellulose, 1 part of carbon nanotubes, 1 part of isocyanate curing agent XP2655, 2 parts of sodium dodecylbenzene sulfonate, 3 parts of leveling agent GLP388, and 60 parts of solvent; The solvent is a mixture of polyvinyl alcohol, n-butanol and deionized water in a volume ratio of 2:5:3.
[0030] The preparation method is as follows: S1: hydroxypropyl methylcellulose and carbon nanotubes are mixed and ground, then dissolved in sodium dodecylbenzene sulfonate, and stirred in a stirrer for 0.5 h at a stirring speed of 400 r / min to obtain a mixed solution A; S2: dissolving epoxy resin and perfluorosulfonic acid resin in a solvent, stirring in a mixer for 0.5 h at a stirring speed of 400 r / min to form a mixed solution B; S3: Mix the mixed liquid A and the mixed liquid B, continue stirring for 2 hours, add a curing agent and a leveling agent during the stirring process, and place at 40° C. for 2 hours after the stirring to obtain an antistatic coating.
[0031] Comparative Example 3 This comparative example provides an antistatic coating, which includes the following components by weight: 30 parts of bisphenol A epoxy resin, 10 parts of perfluorosulfonic acid resin, 1 part of polyaniline modified carbon nanotubes, 1 part of isocyanate curing agent XP2655, 2 parts of sodium dodecylbenzene sulfonate, 3 parts of leveling agent GLP388, and 60 parts of solvent; The solvent is a mixture of polyvinyl alcohol, n-butanol and deionized water in a volume ratio of 2:5:3.
[0032] The preparation method is as follows: S1: placing the carbon nanotubes in a mixture of concentrated sulfuric acid and concentrated nitric acid (the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1), ultrasonically treating, then filtering, washing until the filtrate is neutral, drying, grinding, and setting aside to obtain pretreated carbon nanotubes; S2: Add aniline to 1wt% concentrated sulfuric acid and stir thoroughly for 1h to obtain an acidic solution of aniline; S3: adding the pretreated carbon nanotubes to an acidic solution of aniline at 1 wt%, ultrasonically dispersing for 2 h, then adding ammonium persulfate and continuing ultrasonication for 1 h (the mass ratio of carbon nanotubes to ammonium persulfate is 1:5), to obtain polyaniline-modified carbon nanotubes; S4: dissolving polyaniline-modified carbon nanotubes in sodium dodecylbenzene sulfonate, stirring in a stirrer for 0.5 h at a stirring speed of 400 r / min to obtain a mixed solution A; S5: dissolving epoxy resin and perfluorosulfonic acid resin in a solvent, stirring in a stirrer for 0.5 h at a stirring speed of 400 r / min to form a mixed solution B; S6: Mix the mixed solution A and the mixed solution B, continue stirring for 2 hours, add a curing agent and a leveling agent during the stirring process, and place at 40° C. for 2 hours after the stirring to obtain an antistatic coating.
[0033] Performance Test: The antistatic coatings prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were coated, and then the performance test was performed. The coating method was: coating on a pretreated aluminum plate using a high voltage electrostatic method, the coating thickness was 60 μm, and the coating was cured at 220°C for 12 minutes to obtain a coating. The test of surface resistance (Ω) was in accordance with GB / T1410-2006: the test of wear resistance was in accordance with GB / T1768-2006; the test of tensile strength was in accordance with GB / T16777-1997, and the results are shown in Table 1.
[0034] Table 1
Claims
1. An antistatic coating, characterized in that: By weight, it includes the following components: 20-40 parts of epoxy resin, 10-15 parts of perfluorosulfonic acid resin, 1-3 parts of hydroxypropyl methylcellulose, 0.5-2 parts of polyaniline modified carbon nanotubes, 1-2 parts of curing agent, 0.5-5 parts of dispersant, 3-5 parts of leveling agent, and 55-70 parts of solvent.
2. The antistatic coating according to claim 1, characterized in that: The preparation method of polyaniline modified carbon nanotubes is as follows: The carbon nanotubes are placed in a mixed solution of concentrated sulfuric acid and concentrated nitric acid, subjected to ultrasonic treatment, and then filtered and washed until the filtrate is neutral, dried, ground, and set aside to obtain pretreated carbon nanotubes; Add aniline to 0.5-2 wt% concentrated sulfuric acid and stir thoroughly for 1-2 hours to obtain an acidic solution of aniline; The pretreated carbon nanotubes were added into an acidic solution of aniline at 1-3 wt%, ultrasonically dispersed for 2-3 hours, and then ammonium persulfate was added and ultrasonicated for 1-2 hours to obtain polyaniline-modified carbon nanotubes.
3. The antistatic coating according to claim 2, characterized in that: The volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1; the mass ratio of carbon nanotubes to ammonium persulfate is 1:5-10.
4. The antistatic coating according to claim 1, characterized in that: The epoxy resin is at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, polyphenol glycidyl ether epoxy resin, aliphatic glycidyl ether epoxy resin, glycidyl ester epoxy resin and heterocyclic epoxy resin.
5. The antistatic coating according to claim 1, characterized in that: The curing agent is an isocyanate curing agent.
6. The antistatic coating according to claim 1, characterized in that: The dispersant is at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and polyvinyl pyrrolidone.
7. The antistatic coating according to claim 1, characterized in that: The leveling agent is any one of leveling agent GLP388, leveling agent GLP588, and leveling agent GLP788.
8. The antistatic coating according to claim 1, characterized in that: The solvent is a mixture of polyvinyl alcohol, n-butanol and deionized water, and the volume ratio of polyvinyl alcohol, n-butanol and deionized water is 2:5:
3.
9. The method for preparing the antistatic coating according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1: mixing hydroxypropyl methylcellulose and polyaniline-modified carbon nanotubes, grinding them, dissolving them in a dispersant, and stirring them for 0.5-1h to obtain a mixed solution A; S2: dissolving epoxy resin and perfluorosulfonic acid resin in a solvent and stirring for 0.5-1h to form a mixed solution B; S3: Mix the mixed liquid A and the mixed liquid B, continue stirring for 2-3 hours, add the curing agent and the leveling agent during the stirring process, and place at 40-45°C for 1-2 hours after the stirring to obtain the antistatic coating.
10. The preparation method according to claim 9, characterized in that: The stirring process is carried out in a stirrer at a stirring speed of 400-550 r / min.